National museum dimensions of national identity construction - حەمەخان, م. شیروان عەلی حەمەخان; فتاح, م. ئاوات سعید فتاح (Sulaimani Journal for Humanities, 2025)
Museums in the West emerged after the fourteenth century. In the seventeenth century, especially after the French Revolution, museums were presented as national institutions and places for social education. After the 19th century, the National Museums played a critical role in forming nation-states. Their exhibitions brought together the nations' history, traditions, and culture, thereby creating a sense of unity and togetherness. Obviously, these museum characteristics must be seen within the framework of the formation of the nation-state and the colonial process. In the late twentieth century, this dimension of the museum faced criticism as the museum institution presented itself as the creator of national identity and formal education. A considerable number of community groups, such as Young people, women, and ethnic minorities, are not accommodated in these institutions. These criticisms in the 20th century led museums to rebuild themselves differently.
Keywords: Museum; National Museum; National Identity